Preliminary study of the acoustic behavior concerning an innovative prototype for indoor modular partitioning - Simões, G. (2015)
This paper presents a preliminary acoustic study concerning the development of the first prototype of a patented removable module for interior partitioning. It is a prefabricated, vertical element for division of interior spaces that does not require the use of gutters or technical support. A set of such modules, linearly disposed, will create a division, allowing the personalization of any indoor area, including open office spaces, rooms, among others. The main characteristic that distinguishes this element from the existing solutions available on the market is that its mobility relies exclusively on a set of integrated bearings at the base of each module. Through an incorporated elevation system, the user can lower the module, move it to the desired position and re-elevate it until pressed against the ledge of the ceiling, making it stable. In this sense, and taking into account its acoustic behavior, several tests were made in the LNEC acoustics lab. Airborne sound insulation tests for different typologies of the prototype were conducted, according to the applicable standards EN ISO 354:2003, EN ISO 717-1:2013 and EN ISO 10140-2:2010. Some important conclusions and analysis of the prototype viability were extracted.